"One Belt One Road" and the geopolitics of empire. Issue 3 (3rd July 2019) - Baik, Jiwoon
ABSTRACT: The Belt and Road Initiative (BRI), a grand design proposed by China in 2013, aims at a fundamental geopolitical remapping. Coping with modern geopolitics that the Western world has championed, BRI attempts to overturn the relationship between land and sea, replacing the Pacific Ocean with Eurasia in the center. This shift creates different spatial conception from the one that accompanied modern nomos. By creating infinitely expandable and connectible space with no boundary between inside and outside, BRI resonates with Empire Discourse. Its ultimate destination is to connect China's historical civilization with Chinese socialism, and then to bring to completion of the mission of overcoming the capitalist system. However, it is doubtful whether Chinese socialism, having empire as its soul and BRI as its body, can be a solid alternative to the capitalist regime. Empire-BRI discourse loops ceaselessly double in upon itself within the self-centered circuit despite its insistence on going beyond modernity.